ONE-DRIVE SEBAGAI SOLUSI CERDAS TRANSFORMASI PENYIMPANAN DAN KOLABORASI DOKUMEN AKADEMIK DI SMK BINTANG NUSANTARA PONDOK AREN TANGERANG SELATAN BANTEN - Cendra Harmon; Iis Aisyah; Aulia Ikhsan (Abdi Jurnal Publikasi, 2025)
SMK Bintang Nusantara in Pondok Aren, South Tangerang, faces challenges in managing academic documents and fostering collaboration among students in the digital era. The main issues include a lack of understanding regarding the use of storage and collaboration technology, inadequate technological infrastructure, and low student interaction in learning activities. To enhance the digital skills of students and teachers, this community service program (PkM) is planned to take place over three months, from January to March 2025. The primary beneficiaries of this initiative are the students and teachers at SMK Bintang Nusantara. To address these challenges, this PkM proposes the implementation of OneDrive as an intelligent solution for transforming academic document storage and collaboration. The proposed solution includes several strategic steps: providing training on OneDrive usage for students and teachers to improve digital literacy, ensuring adequate technological infrastructure, integrating OneDrive into the curriculum through collaborative projects, developing accessible digital content, establishing a learning community to support collaboration, conducting regular evaluations and feedback sessions, partnering with third parties for technical support, and raising awareness of digital ethics.